PEMBELAJARAN AKUNTANSI BERBASIS MEDIA PAPAN CATUR DIPANDU DENGAN SHORT CARD UNTUK SISWA SMK RISTEN IMMANUEL II - Agustina, Marsiana; Achmadi, Achmadi; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to know the effectiveness of chess as a learning media to improve studentsâ€™ ability in accountancy of commercial company with accountancy students grade X in SMK Kristen Immanuel II Sungai Raya. The method used in this research is experimental research of One-Shot Case Study.The subject of this research is accountancy students grade X in SMK Immanuel II Sungai Raya with students number is 39 students. Technique of data collecting used is direct observation., direct communication, measurement, and documenter study. Tools of data collecting used were observation sheet, test, and interview guide. The result of this research which have been carried out 4 times meeting shows the average score of students ability progress improve in every meeting. In the first meeting is 63.55, in the second meeting is 64.21, the third meeting is 65.10, and the fourth meeting is 66.32 which have score improvement in every meeting is 2.77. From the observation result, it has been known that tha average of the ability in the first meeting is 63.55 and in the fourth meeting is 66.32 with standard deviation of the first meeting is 6.826. From the result, it obtained the effect size score is 0.40 bcause 0.2 < 0.40 < 0.8, thus the effect size score categorize as moderate.Â It is shows that chess as learning media to improve students ability in accountancy of commercial companyÂ for accountancy students grade X in SMK Immanuel II Sungai Raya is effective.Keywords: Chess as learning media, ability progress, accountancy of commercial company learning